Psychological distress is associated with altered cognitive functioning in family caregivers of patients with disorders of consciousness - Moretta, P.; Masotta, O.; Crispino, E.; Castronovo, G.; Ruvolo, S.; Montalbano, C.; Loreto, V.; Trojano, L.; Estraneo, A. (Brain injury, 2017)
Objectives: To analyse the possible presence of reduced cognitive efficiency in family caregivers of patients with prolonged disorders of consciousness (DOC). Subjects: The participants were 27 caregivers of 25 patients with DOC admitted to the severe brain injury units of the ICS Maugeri, Institutes of Telese Terme and Sciacca, Italy. Methods: We examined cognitive functions such as short- and long-term memory, executive functions and attention by means of standardized tests. We also assessed features of psychological distress such as anxiety, depression, psychophysiological symptoms, prolonged grief disorder, psychological burden and quality of life. All scores on neuropsychological tests were compared with those of the 15 matched control subjects. Results: Enrolled family caregivers showed high frequency of clinically relevant depressive symptoms and anxiety; half of them met the criteria for prolonged grief disorder. Caregivers achieved scores lower than the matched controls on tests for selective attention, verbal fluency and long-term spatial memory. Conclusions: Family caregivers' burden is associated with a reduced efficiency of selected executive measures and visuospatial learning. These results emphasize the need for appropriate psychological and cognitive supporting therapies for family caregivers of patients with DOC, also considering their delicate involvement in clinical decision-making and in providing care.